Procedural Handling of Monopoly Practices and Unfair Business Competition Cases after the Enactment of Business Competition Supervisory Commission Regulation No. 2 of 2023 - Arihta Esther Br Tarigan; Syafrida Syafrida (Universitas Muhammadiyah Tangerang, 2025)
The enactment of Regulation No. 2 of 2023 issued by the Business Competition Supervisory Commission marks a significant reform in the procedural law governing the handling of monopoly practices and unfair business competition cases in Indonesia. This regulation restructures the procedural framework applied by the Business Competition Supervisory Commission, particularly with regard to case initiation, investigation, examination, adjudication, and the enforcement of administrative decisions. This study aims to examine the procedural implications of Regulation No. 2 of 2023 and its contribution to enhancing due process of law, legal certainty, and the effectiveness of competition law enforcement. This study employs a normative juridical method by analyzing statutory regulations, legal doctrines, and principles relevant to administrative adjudication and competition law procedures. The findings indicate that Regulation No. 2 of 2023 introduces clearer procedural stages and strengthens procedural safeguards, thereby promoting transparency and accountability in the handling of competition cases by the Business Competition Supervisory Commission. Nevertheless, several challenges remain, particularly concerning the balance between administrative efficiency and the protection of business actors’ procedural rights, including the right to defense and the right to a fair hearing. This study concludes that Regulation No. 2 of 2023 plays a crucial role in the development of procedural competition law in Indonesia. However, continuous evaluation and refinement are necessary to ensure consistency with fundamental principles of due process and good governance in competition law enforcement.